Perancangan Interior Pusat Batik dan Kerajinan Khas Jawa Timur di Surabaya (Showroom DEKRANASDA Jawa Timur) - Rosaline, Michelle; Honggowidjaja, Stephanus P (Intra, 2015)
This east java batik and handicraft center (east java DEKRANASDA showroom) is a bulding that has a purpose to help the sales rating of the small, middle end enterpreneurs in east java. The east java batik and handicraft center provides showroom concept to display and to sell the products for those potential enterpreneurs by holding the handicraft products, batiks, embroideries, moslem weavings, jewelries or accesorries, home decorations, processed foods, aromatherapy, and many more with no charge at all.This design is using an original site of east java DEKRANASDA showroom that is located at kedungdoro street 86-90, Surabaya. This design is expected to bring out the special characteristics of east java handicrafts so locals and foreigners can understand and be interested in them and by doing so, advancing the economical state of the small, middle end enterpreneurs. This design, with all those applications included, provides an east java batik and handicraft centre as an interesting shopping destination with local content expressed.